Intercultural Theology vis-à-vis Ecumenical and Interreligious Dialogue - Anthony, Francis-Vincent (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The scope of the Special Issue Volume is to explore innovative aspects of intercultural theology in relation to ecumenical and interreligious dialogue. The efforts made by scholars in their thirteen contributions can help overcome the confessional or sectarian view of intercultural theology and find its full significance and rightful place in close association with ecumenism, interreligiousity and interdisciplinarity. The contributions of the authors, in fact, bring into dialogue various religious traditions (Christianity, Hinduism, Islam, African religion, Confucianism), various Christian denominations (Catholic, Orthodox, Protestant, Pentecostal/Charismatic and Independent churches) and diverse socio-cultural linguistic contexts (Russian, Greek, South African, Asian, Indian, Chinese, post-colonial) and interdisciplinary perspectives (theological, philosophical, practical/pastoral, spiritual, catechetical and educational). In this way, the present volume adds to the existing literature on intercultural theology and seeks to enhance cosmotheandric communion and well-being.